2022
DOI: 10.33801/fe.v26i2.19884
|View full text |Cite
|
Sign up to set email alerts
|

Firm registration among White- and Latino-owned employer enterprises

Abstract: This study examines the scope and determinants of firm registration among employer firms of White-owned businesses (WOBs) and Latino-owned businesses (LOBs) in the US. The primary data is derived from the 2020 Stanford Latino Entrepreneurship Initiative nationally representative survey of 3,500 WOBs and 4,145 LOBs. The determinants of firm registration are derived from entrepreneur demographics and firm characteristics, utilizing a binomial logistic regression to predict the odds of group membership of (un)reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…These variables were selected because they have been shown to significantly impact LOBs. Pisani (2022a) showed that LOB registration is related to the size of the firm and its annual sales revenue, among other things. Pisani and Morales (2020) linked the formal registration of LOBs to several business owner and business characteristics, and Orozco (2020) found a connection between the language used in the business and the business's success.…”
Section: Factors Influencing the Success Of Latino-owned Small Busine...mentioning
confidence: 99%
See 1 more Smart Citation
“…These variables were selected because they have been shown to significantly impact LOBs. Pisani (2022a) showed that LOB registration is related to the size of the firm and its annual sales revenue, among other things. Pisani and Morales (2020) linked the formal registration of LOBs to several business owner and business characteristics, and Orozco (2020) found a connection between the language used in the business and the business's success.…”
Section: Factors Influencing the Success Of Latino-owned Small Busine...mentioning
confidence: 99%
“…Two areas of research into Latino entrepreneurship that provide a foundation for this paper are business informality and the enclave. In a recent paper, Pisani (2022a) found that formal registration of LOBs depends on the age of the firm, education of the owner, the region of the US, number of employees, and the sales revenue of the business. Similarly, Pisani and Morales (2020) examined informality and business performance of LOBs in the US and found that firm registration was linked to education, gender, and clientele ethnicity.…”
Section: Factors Influencing the Success Of Latino-owned Small Busine...mentioning
confidence: 99%